Declining Fixed Investment and Increasing Financial Investment of Korean Corporations - Daehwan Kim; Sunhee Kwon; Jai-Won Ryou (East Asian Economic Review (EAER), 2019)
This paper aims to determine factors causing the stagnation of Korean firms' fixed investment after the global financial crisis, using panel data for the period of 1999-2016. Fixed investment remained sensitive to cash flow and Tobin's q although their effects decreased after the global financial crisis. A decreasing trend of cash flow and an increase in Tobin's q since the early 2000's imply that the worsening cash flow was a major factor behind the sluggish investment after the crisis. Meanwhile, debt-equity ratio remained significant for non-chaebol affiliated firms, reflecting disparity in access to external financing. Volatility of stock returns also became insignificant after the crisis, casting doubt on the argument that uncertainty was a major factor contributing to the decline of fixed investment. Analysis of financial investment confirmed the significant effect of cash flow, larger than that on financial investment than on fixed investment. In particular, debt repayment and other financial investment, except share repurchase, were sensitive to cash flow. However, the substitution of fixed investment by financial investment is a consequence, rather than a cause of declining fixed investment.
Keywords: E22; G31; G32; 330; Stagnant Fixed Investment; Financial Investment; Cash Flow; Tobin's q; Global Financial Crisis